Metabolome adaptation and oxidative stress response of common carp (Cyprinus carpio) to altered water pollution levels - Koubová, Anna; Van Nguyen, Tuyen; Grabicová, Kateřina; Burkina, Viktoriia; Aydin, Farah Gönül; Grabic, Roman; Nováková, Petra; Švecová, Helena; Lepič, Pavel; Fedorova, Ganna; Randák, Tomáš; Žlábek, Vladimír (Environmental pollution (Barking, Essex, 2022)
Treated wastewater ponds (TWPs) serve as recipients and passive tertiary treatment mediators for recycled water. These nutrient-rich habitats are increasingly utilised in aquaculture, nevertheless multiple loads of various contaminants with adverse effects on aquatic fauna, including fish, have been recorded. In the present study, we investigated the effects of fish transfer in response to altered levels of pollution on liver metabolic profiles and tissue-specific oxidative stress biomarkers during short- and long-term exposure. In a field experiment, common carp (Cyprinus carpio) originating in severely polluted TWP were restocked after one year to a reference pond with a background pollutant concentration typical of the regional river. In contrast, fish that originated in the reference pond were restocked to TWP. Fish were sampled 0, 7, 14, 60, and 180 days after restocking and fish liver, kidney, intestine, and gill tissues were subjected to biomarker analysis. Pharmaceutically active compounds (PhACs) and metabolic profiles were determined in fish liver using liquid chromatography high-resolution mass spectrometry (LC-HRMS). Fish transferred from reference to polluted pond increased the antioxidant response and absorbed PhACs into metabolism within seven days. Fish liver metabolic profiles were shifted rapidly, but after 180 days to a lesser extent than profiles in fish already adapted in polluted water. Restocked fish from polluted to reference pond eliminated PhACs during the short phase within 14 days, and the highest antioxidant response accompanied the depuration process. Numerous elevated metabolic compounds persisted in such exposed fish for at least 60 days. The period of two weeks was suggested as sufficient for PhACs depuration, but more than two months after restocking is needed for fish to stabilise their metabolism. This study contributed to determining the safe handling with marketed fish commonly restocked to wastewaters and clarified that water pollution irreversibly altered fish metabolic profile.
Keywords: játra; Oxidative Stress; Metabolic profile; oxidační stres; Restocked fish; Metabolome; Antioxidant enzymes; Treated wastewater pond; kapři; Water Pollution; Antioxidants; zvířata; Wastewater; Carps; metabolom; antioxidancia; Waste Water; Liver; voda; Water Pollutants, Chemical; znečištění vody; odpadní voda; Animals; Water; Pharmaceuticals; chemické látky znečišťující vodu